A vasculature-resident innate lymphoid cell population in mouse lungs - Simon Shirley; Hiroshi Ichise; Vincenzo Di Natale; Jiacheng Jin; Christine Wu; Raymond Zou; Wanwei Zhang; Yinshan Fang; Yingyu Zhang; Miao Chen; Sophia Peng; Uttiya Basu; et al. (Nature Communications)
Abstract Tissue-resident immune cells such as innate lymphoid cells (ILC) are known to reside in the parenchymal compartments of tissues and modulate local immune protection. Here we use intravascular cell labeling, parabiosis and multiplex 3D imaging to identify a population of group 3 ILCs in mice that are present within the intravascular space of lung blood vessels (vILC3). vILC3s are distributed broadly in alveolar capillary beds from which inhaled pathogens enter the lung parenchyma. By contrast, conventional ILC3s in tissue parenchyma are enriched in lymphoid clusters in proximity to large veins. In a mouse model of pneumonia, Pseudomonas aeruginosa infection results in rapid vILC3 expansion and production of chemokines including CCL4. Blocking CCL4 in vivo attenuates neutrophil recruitment to the lung at the early stage of infection, resulting in prolonged inflammation and delayed bacterial clearance. Our findings thus define the intravascular space as a site of ILC residence in mice, and reveal a unique immune cell population that interfaces with tissue alarmins and the circulating immune system for timely host defense.